Probability of Alzheimer's disease in breast cancer survivors based on gray‐matter structural network efficiency. Issue 1 (1st November 2017) - Kesler, Shelli R.; Rao, Vikram; Ray, William J.; Rao, Arvind
Abstract: Introduction: Breast cancer chemotherapy is associated with accelerated aging and potentially increased risk for Alzheimer's disease (AD). Methods: We calculated the probability of AD diagnosis from brain network and demographic and genetic data obtained from 47 female AD converters and 47 matched healthy controls. We then applied this algorithm to data from 78 breast cancer survivors. Results: The classifier discriminated between AD and healthy controls with 86% accuracy ( P < .0001). Chemotherapy‐treated breast cancer survivors demonstrated significantly higher probability of AD compared to healthy controls ( P < .0001) and chemotherapy‐naïve survivors ( P = .007), even after stratifying for apolipoprotein e4 genotype. Chemotherapy‐naïve survivors also showed higher AD probability compared to healthy controls ( P = .014). Discussion: Chemotherapy‐treated breast cancer survivors who have a particular profile of brain structure may have a higher risk for AD, especially those who are older and have lower cognitive reserve. Highlights: Chemotherapy is associated with increased risk for Alzheimer's disease. Apolipoprotein genotype moderates the risk for cognitive decline. Brain structure is a useful biomarker of Alzheimer's disease probability.